Bezpečnost provozu na komunikacích - Šimicová, Jitka (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2015)
V době intenzivního provozu na komunikacích se jedním z nejdůležitějších témat stává bezpečnost provozu. Předkládaná diplomová práce se věnuje rozboru různých činitelů, které se právě na bezpečnosti provozu na komunikacích v České republice podílejí. Práce vychází ze srovnávací analýzy dopravní nehodovosti za vymezené období a zajímá se o to, jak různé faktory (zvláště technické parametry vozů a lidské chování) ovlivňují bezpečnost na silnicích.

In the era of the intensive operation on the communication, a question of the safety of the operation becomes one of the most important topics. This thesis deals with an analysis of the various factors, which just participate in the safety of operation on road in the Czech Republic. The thesis results from the comparative analysis of the traffic accident frequency in the allotted period and it takes an interest in how different factors (especially technical parameters of vehicles and human behaviour) influence the safety on highways.
Road Safety
Keywords: bezpečnost provozu – dopravní nehodovost – české komunikace; safety of operation – traffic accident frequency – Czech roads